Carbon crime in the voluntary market: an exploration of modernization themes among a sample of criminal and non-criminal organizations - McKie, Ruth E. (Critical criminology, 2015)
The international voluntary carbon market allows economic actors to profit financially by selling carbon reduction projects (as carbon credits) in the marketplace. The objective of this work is to examine the ideology of that market and its implications for crime and climate change. More specifically, we compare advertising messages for two sets of actors in the voluntary carbon market: criminal and non-criminal organizations. To carry out this analysis we draw upon a grounded theory approach to analyze marketing websites for a sample of organizations that sell credits. We discover that overall, organizations draw upon ecological modernization ideology to provide opportunities to gain access to investors and victims by emphasizing (1) sustainability; (2) ethical behaviour; (3) economic development; and, (4) technological innovation. Importantly, statistical analyses failed to differentiate between the forms of modernization ideology employed by legal and illegal actors.